Disease-modifying rdHSV-CA8* non-opioid analgesic gene therapy treats chronic osteoarthritis pain by activating Kv7 voltage-gated potassium channels - Zhuang, Gerald Z.; Goins, William F.; Kandel, Munal B.; Marzulli, Marco; Zhang, Mingdi; Glorioso, Joseph C.; Kang, Yuan; Levitt, Alexandra E.; Sarantopoulos, Konstantinos D.; Levitt, Roy C. (Frontiers in Molecular Neuroscience, 2024)
Chronic pain is common in our population, and most of these patients are inadequately treated, making the development of safer analgesics a high priority. Knee osteoarthritis (OA) is a primary cause of chronic pain and disability worldwide, and lower extremity OA is a major contributor to loss of quality-adjusted life-years. In this study we tested the hypothesis that a novel JDNI8 replication-defective herpes simplex-1 viral vector (rdHSV) incorporating a modified carbonic anhydrase-8 transgene (CA8*) produces analgesia and treats monoiodoacetate-induced (MIA) chronic knee pain due to OA. We observed transduction of lumbar DRG sensory neurons with these viral constructs (vHCA8*) (~40% of advillin-positive cells and ~ 50% of TrkA-positive cells colocalized with V5-positive cells) using the intra-articular (IA) knee joint (KJ) route of administration. vHCA8* inhibited chronic mechanical OA knee pain induced by MIA was dose- and time-dependent. Mechanical thresholds returned to Baseline by D17 after IA KJ vHCA8* treatment, and exceeded Baseline (analgesia) through D65, whereas negative controls failed to reach Baseline responses. Weight-bearing and automated voluntary wheel running were improved by vHCA8*, but not negative controls. Kv7 voltage-gated potassium channel-specific inhibitor XE-991 reversed vHCA8*-induced analgesia. Using IHC, IA KJ of vHCA8* activated DRG Kv7 channels via dephosphorylation, but negative controls failed to impact Kv7 channels. XE-991 stimulated Kv7.2–7.5 and Kv7.3 phosphorylation using western blotting of differentiated SH-SY5Y cells, which was inhibited by vHCA8* but not by negative controls. The observed prolonged dose-dependent therapeutic effects of IA KJ administration of vHCA8* on MIA-induced chronic KJ pain due to OA is consistent with the specific activation of Kv7 channels in small DRG sensory neurons. Together, these data demonstrate for the first-time local IA KJ administration of vHCA8* produces opioid-independent analgesia in this MIA-induced OA chronic pain model, supporting further therapeutic development.